Guidelines to practice in hospitals at home : safe and effective continuous infusion pumps substantially increased penicillin use in erysipelas treatment - Metsä-Simola, Niina; Saarenketo, Jenni; Lehtonen, Henri; Broman, Niklas; Häggblom, Tony; Björklöf, Pia; Sariola, Salla; Valta, Maija P (Oxford University Press, 2025)
Hospitals at home are increasingly offering outpatient parenteral antimicrobial therapy (OPAT) in an attempt to reduce costly inpatient care, but these settings favour broad-spectrum antibiotics that require less frequent dosing than penicillin. Benzyl penicillin could be delivered via continuous infusion pumps (eCIPs), but studies on their safety and efficacy in OPAT are scarce, and it remains unclear how much the availability of eCIPs increases penicillin use in real-life settings. We examined 462 electronic healthcare records of erysipelas patients treated between January 2018 and January 2022 in a large Finnish OPAT clinic. Average marginal effects from logistic models were estimated to assess how the introduction of eCIPs in December 2020 affected penicillin use and to compare clinical outcomes between patients with and without eCIPs. Introduction of eCIPs increased the predicted probability of penicillin treatment by 36.0 percentage points (95% confidence interval 25.5-46.5). During eCIP implementation, patients who received an eCIP had 73.1 (58.0-88.2) percentage points higher probability than patients without an eCIP to receive penicillin treatment. They also had about 20 percentage points higher probability to be cured at the time of discharge and 3 months after it. Patient and nurse satisfaction regarding eCIPs was very high. Benzyl penicillin eCIP treatment is effective and safe, and substantially increases the use of penicillin instead of broad-spectrum antibiotics. To reduce the risk of antimicrobial resistance, eCIPs could increasingly be promoted for use in OPAT clinics, and there should be adequate education and support in their implementation.